PERBEDAAN PENAFSIRAN “ALASAN SANGAT MENDESAK” DALAM PERMOHONAN DISPENSASI KAWIN (Kajian Penetapan Nomor 0034/Pdt.P/2020/PA.Kr dan Penetapan Nomor 0078//Pdt.P/2021/PA.Kr) - Firman Nugraha , Rizky; Syahputra, Alfi (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2024)
This research is motivated by the existence of two judges' decisions at the Krui Religious Court Class II, West Lampung regarding the marriage dispensation case. The type of research used in this study is library research which is descriptive analysis with a qualitative approach. The results of the study show that the judge in case Number 0034/Pdt.P/2020/Pa.Kr granted the marriage dispensation application using a systematic and grammatical interpretation method because the very urgent reasons had been met, namely formal and administrative requirements and by granting the marriage dispensation, it could minimize or even eliminate damage rather than allowing the relationship to continue without a marriage bond. Meanwhile, the judge in case Number 0078/Pdt.P/2021/PA.Kr rejected the marriage dispensation application using the historical and comparative interpretation method. Although formally and administratively the application was fulfilled, materially the judge was of the opinion that the very urgent reasons for the marriage had not been fulfilled, due to physical unpreparedness, psychological immaturity and economic instability. In fact, there will be greater potential for harm if marriage is forced.